Estruturação e consolidação do tecnosinos – construção do portal de inovação - Righi, Mariane Zanini (Universidade do Vale do Rio dos Sinos, 2015)
This paper aims to present the structuring of project plan and consolidation of Tecnosinos, Technology Park located in São Leopoldo / RS, through the construction of its new headquarters, named Innovation Portal. The developed project is in line with the requirements established by the project sponsor. The plan includes the following structure: plans of integration management, scope, time, cost, quality, resources, communications, risk and acquisitions, elements that are necessary to develop a good project management, according to the practices addressed in the PMBOK Guide.
Keywords: Plano de gerenciamento; Projeto; Inovação; Escopo; Custo; Tempo; Management plan; Project; Innovation; Scope; Cost; Time